People and places shaping food procurement among recipients of Supplemental Nutrition Assistance Program (SNAP). (September 2018) - Monteban, Madalena F.; Bess, Kimberly D.; Walsh, Colleen C.; Baily, Heather; Flocke, Susan A.; Borawski, Elaine A.; Freedman, Darcy A.
Abstract: A key gap in existing food environment research is a more complex understanding of the interplay between physical and social contexts, including the influence of social networks on food habits. This mixed methods research examined the nature of social connections at food procurement places among a sample of 30 people receiving Supplemental Nutrition Assistance Program (SNAP) benefits in an urban setting. Results highlight the significance of social connections as motivators to use food places, the value of access to information and other resources at food places, and the role of weak ties with actors within food places to facilitate utilization and interaction. Social connections at the varied places individuals procure food may be leveraged to disseminate information and resources to further healthy food access. Highlights: People are generally social in their food procurement habits. Purely social connections at food procurement places create a positive atmosphere. People value access to information and other resources transmitted through people within food procurement places. Findings highlight the importance of weak ties for nutritional public health interventions.